(3QSGdI aj Yde GdMQhas - (3YHO GdMb Hf EHQGgje Hf eMeO Hf fUQ GHf SHYjf GdETHjdj GdeQSj GdnqQbhWj, bWH GdOjf CHh eMeO,J (B669 (3g` s ((3eMeO Hf eMeO GdHdjSGhi s)
(3ChdgG (B:s
(3hHYO CjgG GdbGjV jLhR GdcdGe GYde Gf GdcdGe eQcH ef GdMQha s
(3BNQgG (B:s
(3hGPcQ GSe edcg ceG HjfJ dc s
(3GdJhKjbGJ GdeQLYjI (B:s
(3GdCYdGe ; NjQ GdOjf GdRQcdj (B, (3J (B1396 (3g` (B/ 1976(3e(B: (3L (B3 - (3U (B280 ; (3eYLe GdeDdajf ; YeQ QVG cMGdI (B, (3J (B1408 (3g` (B/ 1987 (3e(B: (3L (B5 - (3U (B90s
(3eUOQ GbJfGA GdCUd (B:s
(3GeHQhRjGfG (B(B 58) s
Keywords: (3GdMQha h GdChaGbs